Capacitive sensor readout circuit based on sample and hold method - Wandee Petchmaneelumka; Phirapong Phankamnerd; Apinai Rerkratn; Vanchai Riewruja (Energy Reports, 2021)
This paper presents a capacitive sensor readout circuit using sample and hold method. The proposed readout circuit is used to convert capacitance from sensor to DC (direct current) voltage output. The basic structure of readout circuit consists of the pulse generator circuit, differentiator circuit, amplifier circuit, monostable I circuit, monostable II circuit, and sample and hold circuit. The proposed technique is based on the change of time constant from differentiator circuit corresponding to the measurement capacitance. The sample and hold circuit is used for sampling output voltage from differentiator circuit. The output voltage of the proposed readout circuit is proportional to measurement capacitance. The standard capacitors with different capacitance are used to test the proposed converter performance. Experimental results show that the proposed readout circuit can convert measurement capacitance to output voltage with satisfied values, good linearity and high sensitivity.
Keywords: Sensor Technology and Measurement Systems; Acoustic Wave Resonator Technologies; Ultrasonics and Acoustic Wave Propagation